(untitled) (Wudil Journal of Science and Technology Education, 2025)
Education remains a vital engine of economic growth and national development. In Kano State, persistent educational decline led to the declaration of a State of Emergency on Education to address systemic deficiencies. This study critically examines the successes and challenges recorded in the education sector following this intervention. The study adopted a descriptive survey design using both qualitative and quantitative methods. Data were collected from 150 respondents comprising teachers, school administrators, and Ministry of Education officials. Descriptive statistics such as frequencies, percentages, and charts were used to analyze the data. Results revealed significant achievements, including school rehabilitation, improved enrollment, and increased teacher recruitment. However, challenges such as inadequate funding, poor infrastructure, insecurity, and socio-cultural barriers continue to impede progress. The study concludes that while notable strides have been made, the sustainability of reforms depends on consistent funding, accountability, and strong community participation.